Análisis temporo-espacial y factores asociados a la Fiebre Tifoidea y Paratifoidea de la provincia de El Oro, periodo 2013-2022 - Peña Jiménez, Nixon Ronaldo (2024)
Typhoid and paratyphoid fever are caused by Salmonella enteric serovars Typhi (S. Typhi) and Paratyphi (S. Paratyphi), respectively, and both cause what is known as enteric fever. It manifests with a predominance of fever of several days of evolution, constipation in adults and diarrhea in children. In severe cases of the disease, gastrointestinal problems such as intestinal perforation and hemorrhage can put the patient's life at risk. The objective of this research was to determine the epidemiological evolution of typhoid and paratyphoid fever, through the identification of associated sociodemographic and environmental factors, in the province of El Oro, from 2013 to 2022, in order to propose an educational proposal to promote the reduction of cases of the disease. It was an analytical study, with a mixed approach, retrospective crosssectional cohort, with a universe of 1099 cases registered in the Epidemiological Gazette of the Ministry of Public Health of Ecuador and the National University of Loja. The results obtained show that in the province of El Oro, the disease prevailed in women, in the age group 20-49 years, in the canton of Machala, in the dry season, while in the cold and warm season the prevalence of cases was similar; and the year in which the highest proportional trend is recorded was 2013, finally, an educational digital strategy of prevention for the general population was proposed. In conclusion, it is shown that during the ten years of studies, the prevalence of cases has decreased significantly, but it is necessary to continue with the development of prevention strategies and diagnosis of the disease to avoid resurgence